Modification of carbon containing electrodes by aryldiazonium iodate salts for electroanalysis - Gusar, A.O.; Dorozhko, Ye.V.; Dyorina, K.V.; Korotkova, Ye.I. (Ye.A.Buketov Karaganda State University Publishing house, 2019)
In the work the method of spontaneous chemical modification of a glassy carbon electrode (GCE) with aryl diazonium iodate salts was studied. The adsorption of modifier from the solution was applied for GCE modification. The modification effectiveness assessment was performed for different modifiers under the conditions of modifier concentration varying and the time of electrode keeping in the solution. The cyclic voltammograms of the reversible pair [Fe(CN)6]3–/4– were recorded in the background KCl 0.5 M electrolyte. Modifier surface layers form spontaneously without the application of potentials. The control of thickness and the conductive characteristics of the modified electrode were performed by the adjusting of concentration and the keeping time of the electrode in modifier solution. It has been established that the oxidation and reduction currents of [Fe(CN)6]3–/4– are maximum for the 4-carboxybenzodiazonium iodate modifier of GCE with a concentration of 10 mg•l–1 when the time of keeping the electrode in its solution is for 5 seconds. The increasing of the reversible pair [Fe(CN)6]3–/4– current in the indicated conditions after the modification of 4-carboxybenzodiazonium iodate is associated with an increase in the area of the electroactive electrode surface, by almost 2.5 times. The study of the morphology of the electrode surface of the GCE by the method of scanning electrode microscopy confirmed the presence of a polylayer modifier with a carboxy substituent on the surfaces of a glassy carbon electrode. To confirm the presence of organic functional groups of the 4-carboxybenzodiazonium iodate modifier on the surfaces of the GCE, the reflection spectra of the electrode surfaces were obtained by IR spectroscopy. The method of modifying the GCE with iodate salts of aryldiazonium is simple, rapid, has low costs, and can be used to increase the sensitivity of determining a number of analytes in electroanalyses.
Көміртекқұрамды электродтарды арилдиазонийдің йодты тұздары арқылы электрталдау үшін модификациялау
Модификация углеродсодержащих электродов посредством йодистых солей арилдиазония для электроанализа
Keywords: aromatic diazonium salts; modifiers; glassy carbon electrode; cyclic voltammetry; IR spectroscopy; SEM (scanning electron microscopy); potassium ferrocyanide; spontaneous formation of modifier layer